CdSe Quantum Dots for Solar Cell Devices. (17th April 2012) - Kashyout, A. B.; Soliman, Hesham M. A.; Fathy, Marwa; Gomaa, E. A.; Zidan, Ali A.
Abstract : CdSe quantum dots have been prepared with different sizes and exploited as inorganic dye to sensitize a wide bandgap TiO2 thin films for QDs solar cells. The synthesis is based on the pyrolysis of organometallic reagents by injection into a hot coordinating solvent. This provides temporally discrete nucleation and permits controlled growth of macroscopic quantities of nanocrystallites. XRD, HRTEM, UV-visible, and PL were used to characterize the synthesized quantum dots. The results showed CdSe quantum dots with sizes ranging from 3 nm to 6 nm which enabled the control of the optical properties and consequently the solar cell performance. Solar cell of 0.08% performance under solar irradiation with a light intensity of 100 mW/cm 2 has been obtained. CdSe/TiO2 solar cells without and with using mercaptopropionic acid (MPA) as a linker between CdSe and TiO2 particles despite a V oc of 428 mV, J sc of 0.184 mAcm -2, FF of 0.57, and η of 0.05% but with linker despite a V oc of 543 mV, J sc of 0.318 mAcm -2, FF of 0.48, and η of 0.08%, respectively.